On the use of low-density polyethylene as disposable drip tape for field irrigation. (16th March 2018) - Zhu, Delan; Wu, Shoujun; Guo, Bin
ABSTRACT: In the present study, micro-level analysis of seven months of field irrigation-induced evolution of tensile properties of a disposable drip tape made from a virgin polyethylene mixture and 2 wt% carbon black was conducted. After field irrigation, the molecular weight of the soluble small molecules in the drip tape was reduced, while their content was increased. Meanwhile, the crystallinity of the PE constituents in the drip tape increased, whereas the crystallinity of the non-PE constituents decreased. After the field irrigation, the melting point and the corresponding value caloric of the drip tape increased. During heating, the as-received drip tape showed no weight changes, whereas the drip tape after irrigation showed a continuous small weight loss. The difference in the intrinsic properties of low-density polyethylene, linear LDPE, and high-density polyethylene was the reason for the field irrigation-induced evolution of the mechanical properties of the disposable drip tape.